Intertextuality in Educational Reform: Reflections on Equity in Swedish School Reform - Francia, Guadalupe (Education Policy Analysis Archives, 2008)
This article proposes intertextuality as a conceptual instrument for the deeper understanding of the phenomenon of equity in educational Reform in times of decentralization. This analysis starts from a dynamic vision of education reforms as interactions of texts. To illustrate the use of intertextual analysis of equity in education, this article introduces and discusses the analyzed examples of the educational national policy and of educational practice in the educational reform implemented in the 90?s and currently in force in the compulsory school in Sweden. It is argued that the meaning of equity is never a fixed one; it varies according to the interactions between political texts at a national level and texts of educational practice at communal and school levels.